Selection of Catalysts for Use in a Heterogeneous Catalytic Ozonation System. (3rd March 2020) - Agudelo, Edison Alexander; Cardona G., Santiago Alonso
ABSTRACT: For this article, the authors tested various commercially available materials, such as activated carbon of vegetable origin, kaolin, vermiculite, Portland cement, magnetite and Earth´s Fuller to identify which is the best catalyst in the production of hydroxyl radical. The researchers used oxalic acid as a test compound to quantify the production of hydroxyl radical, taking advantage of the rapid reaction hydroxyl radical (.OH)-oxalic acid, and the very slow reaction ozone-oxalic acid. The best catalyst defined in terms of higher degradation of the oxalic acid (higher production of hydroxyl radical and oxidizing-species) was fixed it to glass spheres using a polymer film technique. The combination activated carbon and Portland cement (in a 1:1 ratio w/w) showed it the best performance in the oxalic acid elimination in a ratio catalyst-compound/ozone 900 (w/w), this condition produced a removal of 56% of the mass of oxalic acid initial (1000 mg) in the water treated with ozone over a period of 5 minutes. The main contribution of this article was to discover between some commercial materials, a compound capable to produce hydroxyl radical to manner efficient with the ozone. The synergistic effect of Portland cement in the system activated carbon-ozone increased the production of hydroxyl radicals. Besides their affordability and accessibility, the combined use of activated carbon and Portland cement lead to greater efficiency in the technical implementation of advanced oxidation processes.